Sedentary behaviors, physical activity, and risk of allergic rhinitis and asthma: evidence from cohort and Mendelian randomization studies - Xiaoyu Wang; Yaya Gao; Lin Lou; Wenjie Yang; Wei Xu; Yu Zhao; Jianjun Ren (BMC Pulmonary Medicine)
Abstract Background The causality between movement behaviors [sedentary behavior (SB) and physical activity (PA)] with the prevalence of allergic rhinitis (AR) and asthma remained unclear. This study aimed to examine whether different movement behaviors are risk factors for AR and asthma based on epidemiological and genetic evidence, and to characterize these associations in diverse populations. Methods Based on information of questionnaires and registrations provided by UK Biobank, and large-scale GWAS (Genome-Wide Association Study) data, we designed a cohort study with a follow-up period exceeding 11 years and two-sample Mendelian randomization (MR) analysis to explore the causal associations between movement behaviors (SB and PA) and AR and asthma. Results Compared to participants with low SB, those with increased SB had higher risk for asthma (moderate: HR = 1.04, 95% CI: 1.01–1.08, p = 0.019; high: HR = 1.14, 95% CI: 1.10–1.18, p < 0.001). In contrast, more PA was a preventive factor for asthma (moderate: HR = 0.89, 95% CI: 0.81–0.97, p = 0.006; high: HR = 0.9, 95% CI: 0.83–0.99, p = 0.026). However, no correlation was found between movement behaviors and AR. The consistent associations between movement behaviors and asthma were also confirmed in male, younger (< 60) and older ( > = 60) populations. However, in females, only an association between SB and increased asthma risk was observed, while no protective effect of PA on asthma was identified. Moreover, genetically-predicted causality was observed between SB and asthma as well as PA and asthma by MR analysis (SB: OR = 1.16, 95% CI: 1.04–1.29, p = 0.009; PA: OR = 0.94, 95% CI: 0.88-1.00, p = 0.046), which was consistent with the findings of our cohort studies. Conclusions This study highlights the risk of asthma associated with SB and emphasizes the role of PA in mitigating this risk. However, no significant association was found between movement behaviors and AR. Clinical trial number Not applicable.